Crack initiation and endurance limit of hard steels under multiaxial cyclic loads - Bomas, H.; Kienzler, R.; Kunow, S.; Loewisch, G.; Schroeder, S. (Проблемы прочности, 2008)
The endurance limit and the mechanisms o f fatigue crack initiation in the high cycle regime were
investigated using round specimens o f the bearing steel 52100 under longitudinal forces and
torsional moments and combinations o f these loads. Three specimen types were examined: smooth
specimens and specimens with circumferential notches with radii o f 1.0 and 0.2 mm. The influence
ofmean and multiaxial stresses on the endurance limit can be understood by consideration ofcrack
initiation mechanisms and micro-mechanics. Crack initiation took place at oxides, carbonitrides
and at the surface. The mechanisms ofcrack initiation could be related to the load type: Loads with
rotating principal stresses are more damaging fo r nitrides than fo r oxides. Increasing maximum
stresses are more dangerous fo r nitrides than fo r oxides, and introduce more damage to the surface
than to the nitrides. Normal stresses are more damaging fo r oxides than shear stresses. The
endurance limits were calculated by means o f an extended weakest-link model which combines
volume and surface crack initiation with related fatigue criteria. For volume crack initiation the
criterion o f Dang Van was used. For the correct description o f the competing surface crack
initiation, a new criterion was applied. With this concept, a prediction o f the endurance limit is
possible fo r loads which produce critical planes and range within a limited regime ofstress ratios. Исследованы предел выносливости и механизмы
зарождения усталостных трещин в
многоцикловом режиме, используя круглые
образцы из подшипниковой стали 52100,
подвергаемые действию продольных сил и
крутящих моментов, а также комбинации
этих нагрузок. Использовали гладкие образцы
и образцы с кольцевыми надрезами радиусами
1,0 и 0,2 мм. Влияние средних и
многоосных напряжений на предел выносливости
может быть объяснено с учетом
механизмов зарождения трещин и микромеханики.
Зарождение трещин происходило
на оксидах, карбонитридах и на поверхности.
Механизмы зарождения трещин могут
быть связаны с типом нагрузки: нагрузки
с вращательными главными напряжениями
более деструктивны для нитридов, чем
для оксидов. Возрастающие максимальные
напряжения более опасны для нитридов,
чем для оксидов, и вызывают большие повреждения
поверхности, чем нитридов. Нормальные
напряжения вызывают большее повреждение
оксидов, чем касательные напряжения Пределы выносливости рассчитывали
с помощью модифицированной модели слабого
звена, которая объединяет зарождение
трещин в объеме и на поверхности с соответствующими
критериями усталости. Для
зарождения трещин в объеме был использован
критерий Данг Вана. Для корректного
описания конкурирующего зарождения трещин
на поверхности был применен новый
критерий. С помощью этой концепции можно
предсказать предел выносливости для нагрузок,
которые создают критические плоскости
и диапазон в рамках ограниченного
режима коэффициентов асимметрии цикла.